C-MYC and C-FOS expression changes and cellular aspects of the photodynamic reaction with photosensitizers TMPyP and ClAlPcS2 - Pížová, Klára; Bajgar, Robert; Fillerová, Regina; Kriegová, Eva; Cenklova, Vera; Langová, Kateřina; Konecny, Petr; Kolářová, Hana (Journal of photochemistry and photobiology. B, Biology, 2015)
Photodynamic therapy (PDT) is based on the tumor-selective accumulation of photosensitizer followed by irradiation with light of an appropriate wavelength. After irradiation and in the presence of oxygen, photosensitizer induces cellular damage. The aim of this study was to evaluate effects of two photosensitizers TMPyP and ClAlPcS2 on cell lines to obtain better insight into their mechanisms of action. We determined cell viability, reactive oxygen species (ROS) generation and changes in expression levels of two important early response genes, C-MYC and C-FOS, on tumor MCF7 (human breast adenocarcinoma) and G361 (human melanoma) cell lines and non-tumor BJ cell line (human fibroblast) after photodynamic reaction with TMPyP and ClAlPcS2 as photosensitizers. In addition TMPyP and ClAlPcS2 cellular uptake and clearance and antioxidant capacity of the mentioned cell lines were investigated. We found appropriate therapeutic doses and confirmed that both tested photosensitizers are photodynamically efficient in treatment used cells in vitro. TMPyP is more efficient; it had higher ROS production and toxicity after irradiation by intermediate therapeutic doses than ClAlPcS2. We revealed that both TMPyP and ClAlPcS2-PDT increased C-FOS expression on tumor cell lines (G361 and MCF7), but not on non-tumor BJ cell line. Conversely, both TMPyP and ClAlPcS2-PDT decreased C-MYC expression on non-tumor BJ cell line but not on tumor cell lines. As first we tested these photosensitizers in such extent and we believe that it can help to better understand mechanisms of PDT and increase its efficiency and applicability.
Keywords: Indoles; Organometallic Compounds; Antioxidants; indoly; Porphyrins; Cell Line, Tumor; porfyriny; Up-Regulation; Neoplasms; MFC-7 buňky; nádory; protoonkogenní proteiny c-fos; lidé; organokovové sloučeniny; Proto-Oncogene Proteins c-fos; Proto-Oncogene Proteins c-myc; Photochemotherapy; MCF-7 Cells; upregulace; Photosensitizing Agents; protoonkogenní proteiny c-myc; Reactive Oxygen Species; fotosenzibilizující látky; Light; antioxidancia; reaktivní formy kyslíku; Cell Survival; světlo; viabilita buněk; fotochemoterapie; nádorové buněčné linie; Humans